Intraoperative hydrostatic reduction of intussusception - Chatterjee Uday; Ghosh Ajoy; Basu Ashoke; Mukhopadhyay Partha (Wolters Kluwer Medknow Publications, 2008)
Aims: To find out an easier way of reduction of intussusception during open surgery to avoid unnecessary bowel injury. Materials and Methods: Under general anesthesia, before laparotomy, warm normal saline was infused into the rectum with a Foley catheter and an intravenous drip set maintaining the level of the bottle at 80 cm above the operating table. After opening the abdomen, pressure was applied on the colon filled with normal saline distal to the intussusceptum. The pressure was transmitted to the intussusceptum and the walls of the intussuscipient and caused reduction of intussusception without any injury to the intussuscipient and intussusceptum. This procedure was performed on those patients on whom laparotomy was performed as a primary procedure due to nonavailability of fluoroscopy or ultrasonography. Results: Between August 1998 and July 2005, we had six patients of mean (range) age 11 months (7-17 months). In two cases, at laparotomy, the intussusceptions were found to have already reduced. Conclusions: Gentle finger pressure is necessary for reduction of intussusception. This subjective "gentleness" is dependant on experience of the surgeon and varies from person to person. Focal pressure on the intussuscipient and apex of the intussusceptum by the finger during reduction may be more damaging than the diffusely transmitted hydrostatic pressure even by a less-experienced surgeon. This will avoid the needless resection and anastomosis of the intestine on many occasions.